He Matatika Māori: Māori and Ethical Review in Health Research - Hudson, Maui (Auckland University of Technology, 2004)
Maori aspirations for a better future are inextricably linked to their health and well-being. Research is a central element of any strategy to ensure that the inequalities of today will not be experienced by Maori children of the future. Kaupapa Maori research has been at the forefront of the indigenous challenge to Western research practices which continue to frame Maori as the 'other' and victim blame by measuring differences to non-Maori and then attribute identified negative differences to Maori deficit. A kaupapa Maori framework validates Maori realities and enables the development of research processes that are based on a Maori worldview and endorse Maori values and beliefs. Proponents of distinctly Maori research methodologies have questioned the appropriateness of ethical review processes that are based on Western concepts of ethics that they contend are incongruent with Maori cultural values and beliefs. Maori ethical issues identified in the literature that arise from this interface have similarities with indigenous ethical themes of respect, control and reciprocity. This qualitative research study was based on a kaupapa Maori approach. The research addressed two main research questions: whether the current system of ethical review in New Zealand is responsive to Maori and how can tikanga Maior inform Maori research ethics. Primary data for this study was drawn from interviews with Maori members of ethics committees and analysed thematically. The major conclusion of this study was that the current ethical review process is limited in its responsiveness to Maori. The research found that Maori values were generally marginalised within ethical review processes that are based on universal ethics derived from a Western value base. A number of key ethical issues for Maori are not addressed appropriately within the current system of ethical review due to the limited parameters, in Maori terms, of the review process. It is essential that Maori issues and concerns be addressed in order for Maori to benefit from the activities of the research sector. Differences exist between Maori and Western concepts of ethics and the inclusion of tikanga Maori within the ethical review process could lead to a more transparent and responsive evaluation and greatly enhance the quality of ethical review of health research in New Zealand. The development of a Maori ethical framework that describes the principles of tikanga Maori and their application within the context of research ethics could provide a culturally appropriate framework for ethical review. Such a framework would address ethical issues of significance for Maori in research. The establishment of a National Maori Ethics Committee and the development of a parallel Maori ethical review pathway would further enhance Maori responsiveness.
Keywords: Maori (New Zealand people); Research; Methodology; Health and hygiene; Research; Hauora; Kupu; Health Studies